Neuroprotective Properties of Bis-Sulfonamide Derivatives Against 6-OHDA-Induced Parkinson's Model via Sirtuin 1 Activity and in silico Pharmacokinetic Properties - Apiraksattayakul, Setthawut; Pingaew, Ratchanok; Prachayasittikul, Veda; Ruankham, Waralee; Jongwachirachai, Papitcha; Songtawee, Napat; Suwanjang, Wilasinee; Tantimongcolwat, Tanawut; Prachayasittikul, Supaluk; Prachayasittikul, Virapong; Phopin, Kamonrat (Frontiers in Molecular Neuroscience, 2022)
Parkinson's disease (PD) is considered one of the health problems in the aging society. Due to the limitations of currently available drugs in preventing disease progression, the discovery of novel neuroprotective agents has been challenged. Sulfonamide and its derivatives were reported for several biological activities. Herein, a series of 17 bis-sulfonamide derivatives were initially tested for their neuroprotective potential and cytotoxicity against the 6-hydroxydopamine (6-OHDA)-induced neuronal death in SH-SY5Y cells. Subsequently, six compounds (i.e., 2, 4, 11, 14, 15, and 17) were selected for investigations on underlying mechanisms. The data demonstrated that the pretreatment of selected compounds (5 μM) can significantly restore the level of cell viability, protect against mitochondrial membrane dysfunction, decrease the activity of lactate dehydrogenase (LDH), decrease the intracellular oxidative stress, and enhance the activity of NAD-dependent deacetylase sirtuin-1 (SIRT1). Molecular docking was also performed to support that these compounds could act as SIRT1 activators. In addition, in silico pharmacokinetic and toxicity profile prediction was also conducted for guiding the potential development. Thus, the six neuroprotective bis-sulfonamides were highlighted as potential agents to be further developed for PD management.